The frequency of insulin resistance calculated upon the basis of a fasting glucose to insulin ratio and characteristics of insulin resistant women with polycystic ovary syndrome - Popovska Dimova, Zhaneta; Krstevska, Brankica (Macedonian Academy of Sciences and Arts/De Gruyter, 2006)
The Polycystic Ovary Syndrome (PCOS) is a common endocrine and metabolic disorder of women of reproductive age, characterized by hyperandrogenism and chronic anovulation. Peripheral insulin resistance (IR) has a crucial role in the pathogenesis of this disorder. A fasting glucose to insulin (G/I) ratio is a simple, reliable, sensitive and specific measurement of insulin sensitivity and is a useful test for the identification of IR in women with PCOS, who have to be treated with insulin sensitizers.
Keywords: polycystic ovary syndrome (PCOS); insulin resistance (IR); glucose to insulin (G/I); body mass index (BMI); sex hormone binding globulin (SHBG)